STEM Based Teaching and Learning Module Development for Year 5 Plant Topics - Bin Mohd Aris, Muhammad Afif; Binti Mansor, Rosnidar (International Journal of Academic Research in Progressive Education and Development, 2023)
STEM is an acronym of science, technology, engineering and mathematic, it is crucial to apply STEM education in recent years of education. Teachers should have their own teaching module that suite their student’s needs. The objective of this study is to create and assess the viability of an educational module for teaching and learning about plants, specifically designed for fifth-grade primary school students. The research employed the Research and Development (R&D) approach, utilizing the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The outcomes of the research (1) demonstrate the successful creation of a teaching and learning module focused on plants for fifth-grade students. (2) The collective agreement percentage derived from the experts amounts to 90.44%. The content validity analysis of the teaching and learning module, based on the ADDIE framework, was assessed by six experts who provided a commendable score, with an average agreement percentage of 88%. (3) The reliability assessment, indicated by Cronbach's alpha coefficient, yielded a value of 0.897. The analysis of the feasibility questionnaire resulted in highly favourable scores of 90.44%. Therefore, the teaching and learning module based on the ADDIE model, focusing on the topic of plants for fifth-grade students, is deemed suitable as a learning medium for primary school students.